The New Neighborhood Senior Center : Redefining Social and Service Roles for the Baby Boom Generation - Weil, Joyce (Book collections on Project MUSE., 2014)
"In this book, ethnographic work at a working-class senior center in Queens, NY, is used as a case study to examine the role of social structure, not only upon the life stories of older individuals attending the center, but in affecting and being affected by changes at the level of the center, from the local community, city, and beyond. The work traces the effects of political, social, and economic institutions, organizations, and neighborhood processes involved in the decision to close, or "shutter," a senior center that was not even part of the Department for the Aging's (DFTA) leaked closure list. The discussion is then expanded to include issues related to the trend of "re-branding," or making existing senior centers more innovative, to attract Baby Boomers (those born between 1946 and 1964). With 7,000 Baby Boomers turning 65 years of age each day in 2011 in the United States, considerable time and effort have been spent making centers appealing to the Baby Boomers. Yet, at the same time, a need is seen to balance the Boomers' center models to also accommodate the needs of a group of more frail or "vulnerable" elders who also rely on the services of senior centers on a daily basis."--